Antibiotic Susceptibility of Biofilm Cells and Molecular Characterisation of Staphylococcus hominis Isolates from Blood - Horsburgh, Malcolm James; Mendoza Olazarán, Soraya Sarahí; Morfín Otero, Rayo; Villarreal Treviño, Licet; Rodríguez Noriega, Eduardo; Llaca Díaz, Jorge Martín; Camacho Ortiz, Adrián; González González, Gloria María; Casillas Vega, Néstor Guadalupe; Garza González, Elvira (2015)
Objectives We aimed to characterise the staphylococcal cassette chromosome mec (SCCmec) type, genetic relatedness, biofilm formation and composition, icaADBC genes detection, icaD expression, and antibiotic susceptibility of planktonic and biofilm cells of Staphylococcus hominis isolates from blood. Methods The study included 67 S. hominis blood isolates. Methicillin resistance was evaluated with the cefoxitin disk test. mecA gene and SCCmec were detected by multiplex PCR. Genetic relatedness was determined by pulsed-field gel electrophoresis. Biofilm formation and composition were evaluated by staining with crystal violet and by detachment assay, respectively; and the biofilm index (BI) was determined. Detection and expression of icaADB Cgenes were performed by multiplex PCR and real-time PCR, respectively. Antibiotic susceptibilities of planktonic cells (minimum inhibitory concentration, MIC) and biofilm cells (minimum biofilm eradication concentration, MBEC) were determined by the broth dilution method. Results Eighty-five percent (57/67) of isolates were methicillin resistant and mecA positive. Of the mecA-positive isolates, 66.7% (38/57) carried a new putative SCCmec type. Four clones were detected, with two to five isolates each. Among all isolates, 91% (61/67) were categorised as strong biofilm producers. Biofilm biomass composition was heterogeneous (polysaccharides, proteins and DNA). All isolates presented the icaD gene, and 6.66% (1/15) isolates expressed icaD. This isolate presented the five genes of ica operon. Higher BI and MBEC values than the MIC values were observed for amikacin, vancomycin, linezolid, oxacillin, ciprofloxacin, and chloramphenicol. Conclusions S. hominis isolates were highly resistant to methicillin and other antimicrobials. Most of the detected SCCmec types were different than those described for S. aureus. Isolates indicated low clonality. The results indicate that S. hominis is a strong biofilm producer with an extracellular matrix with similar composition of proteins, DNA and N-acetylglucosamine; and presents high frequency and low expression of icaD gene. Biofilm production is associated with increased antibiotic resistance.